Analysis of Translation Method in Translating Children’s Storybook - Larasati, Qori (Universitas Islam Negeri Raden Intan Lampung, 2025)
This research aims to translate children’s storybook using the translation method proposed by Newmark. Besides, this translation also aims to introduce foreign cultures to the children especially the Indian culture which is still rarely known. The research method used is descriptive qualitative. This research is conducted by collecting data related to translation especially children’s storybook translation. The result of this research shows that five translation methods proposed by Newmark can be applied in the children’s storybook translation entitled “Sweet Sunday” while the other three translation methods cannot be applied. Those five translation methods are word for word translation, literal translation, semantic translation, free translation, and communicative translation. In conclusion, the translation methods applied to this translation have been considered to produce accurate, acceptable, and readable translations by emphasizing the use of original culture in accordance with the purpose of this translation.